2017
DOI: 10.15419/jmri.27
|View full text |Cite
|
Sign up to set email alerts
|

Health Problems and Health Care Seeking Behaviour of Rohingya Refugees

Abstract: Background: Rohingya refugees are one of the most vulnerable group due to lack of health care system, personal hygiene, shelter, sanitation and violence. Aim: The present study aims to find out the health problems and health care seeking behavior of Rohingya Refugees, to identify the socio-demographic information for such exposure group in relation to age, sex, occupation, living areas, to explore the patient's physical, emotional, perceptions, attitudes and environmental health problems and to bring out healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 5 publications
1
20
2
Order By: Relevance
“…The occupations of most of the females identified as housewives and males worked in agriculture or labor-based occupations. This is similar to a study that [22] found Rohingya refugees on the Thai border reported agriculture or labor-based occupations. In the refugee camps, more than half of the migrants lived without family, we speculate this may be because of lost family members in the violence prior to migrating from Rakhaine [8, 22 -24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The occupations of most of the females identified as housewives and males worked in agriculture or labor-based occupations. This is similar to a study that [22] found Rohingya refugees on the Thai border reported agriculture or labor-based occupations. In the refugee camps, more than half of the migrants lived without family, we speculate this may be because of lost family members in the violence prior to migrating from Rakhaine [8, 22 -24].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the refugees reported literacy challenges. This was not surprising, as Rohingyas receive almost no support for basic education in Myanmar, nor in Bangladesh [21,22]. The occupations of most of the females identified as housewives and males worked in agriculture or labor-based occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Without a functional referral system, it is not possible to provide comprehensive health care to pregnant women and children on time [26]. Previous studies done in the FDMN camps [30,31] showed that the referral pathway was too convoluted, and there was also underutilization of referral services by the beneficiaries. Our study found that the situation has been improved after the introduction of dedicated vehicle service and referral managers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 50 , 51 , 52 , 53 ] conducted by Handicap International and other institutions detail the challenges facing refugee care, a situation that can be extrapolated to the different EU countries: Deficit in diagnosing and identifying the care needs of refugees with a disability, which leads to a considerable waste of time and the transfer of these refugees to reception centers that do not have the resources to guarantee adequate treatment. Legal restrictions that prevent refugees with a disability from accessing regular care services.…”
Section: From Observation To Interventionmentioning
confidence: 99%